Effect of a liberal versus a restrictive pre‐donation blood pressure policy on whole‐blood donor adverse reactions. Issue 4 (18th March 2019) - Salvadori, Ugo; Sandri, Marco; Cemin, Roberto; Al‐Khaffaf, Ahmad; Daves, Massimo; Maniscalco, Francesco; Hueber, Rudolf; Troi, Christina; Griessmair, Astrid; Ploner, Franz; Egger, Karl; Kuehebacher, Gottfried; et al.
Abstract : Background and Objectives: The role of pre‐donation blood pressure (BP) as independent contributor to post‐donation vasovagal reactions (VVRs) is still debated. Differences between a liberal (i.e., inclusion of hypotensive donors) and a restrictive policy (i.e., not accepting hypotensive donors) should be investigated. This study aims to investigate the consequences of a liberal policy in development of VVRs after whole‐blood donations. Materials and Methods: We compared the incidence of VVRs between 2015 (restrictive policy) and 2016 (liberal policy) and the associated risk factors. We evaluated respectively 22 789 vs. 21 676 blood donations obtained from 18 001 blood donors (12 501 donated in both years). Results: Comparing the results we obtained between 2015 and 2016, donations showed an overlap of the cohorts. Two hundred fifteen VVRs (incidence rate 0·48%) were observed, 104 (0·46%) of which in 2015, and 111 (0·51%) in 2016. A preliminary univariate analysis showed that donors with systolic BP <110 mm Hg had a two‐fold risk of VVRs compared to normotensive donors (VVR/donation rate of 0·99% vs. 0·46%; P  = 0·001). The subsequent multivariable logistic regression model showed that VVRs were highly associated with weight, site of collection, age and number of donations, excluding a role for systolic and diastolic BP. Conclusion: A liberal pre‐donation BP policy seems to be safe for blood donors. Our analysis confirms that older donors with higher body‐weight who already had donated blood are unlikely to experience VVRs.